Strategic supply management revisited : competing in an era of rapid change and disruption - Trent, Robert J. (J. Ross Publishing, 2018)
Explaining how to gain a competitive advantage through true collaborative relationships, this book introduces essential supply management concepts, strategies, and practices that are an integral part of surviving and thriving in this unprecedented era of rapid change and disruption. --